Reabilitação protética com associação entre prótese parcial removível e implante dentário: relato de caso - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Medeiros, Rodrigo Antonio de [UNESP]; Laurindo Júnior, Murilo Cesar Bento [UNESP]; Watanabe, Denis [UNESP] (My University, 2013)
Removable partial denture improve functional and aesthetic failures caused by partial loss of teeth, however specific characteristics of each patients can determine the success of treatment, especially with regard to the support of the prosthesis, which may depend on teeth, the combination of teehe and mucosa and currently associated with the dental implants. The aim of this study is report a case in which there was the need of the association, to enable better aesthetics and self-esteem to the patients. After implant placement and fabrication of prosthetic patient reported satisfaction with the rehabilitation treatment, improving their quality of life.

A prótese parcial removível supre falhas funcionais e estéticas causadas pela falta parcial de elementos dentários, no entanto, características específicas de cada paciente podem determinar o sucesso do tratamento, principalmente no que diz respeito ao suporte da prótese, que pode depender de dentes, da associação de dentes e de mucosa, e atualmente da associação com próteses implantossuportadas. O presente estudo objetiva relatar um caso em que houve a necessidade dessa associação, para possibilitar uma melhor estética e auto-estima à paciente. Após a instalação dos implantes e confecção das próteses a paciente relata-se satisfeita com o tratamento reabilitador, melhorando sua qualidade de vida
Prosthetic rehabilitation with association between removable partial denture and dental implant: a case report
Keywords: Dental implant; Partial denture; Mouth rehabilitation; Implante dentário; Prótese parcial; Reabilitação bucal